Diagnostic accuracy of diffusion weighted magnetic resonance imaging (DW-MRI) and transvaginal ultrasonography (TVUS) in assessing myometrial invasion among female patients with endometrial cancer: a systematic review and meta-analysis / Sofea Sarina Mazrul, Mohd Zulfadli Adenan - Mazrul, Sofea Sarina; Adenan, Mohd Zulfadli (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
TVUS is the first imaging technique in determining patient with suspicious of endometrial cancer whereas the most appropriate tool for grading of endometrial cancer is MRI. Recently, DW-MRI gradually becomes a routine in grading endometrial cancer. Thus, the purpose of this study was to compare the diagnostic accuracy of transvaginal ultrasound (TVUS) and diffusion weighted magnetic resonance imaging (DW-MRI) in assessing depth of myometrial invasion in endometrial cancer. An extensive search was performed in Dimension, PubMed and Wiley Online Library guided by PRISMA. Following screening, the eligibility of the studies was checked. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) checklist. The search identified 7 studies (727 patients). Overall, pooled estimated sensitivity and specificity for detecting deep myometrial invasion were 79% (95% confidence interval [CI]=72%-85%) and 84% (95% CI=64%-94%) for TVUS, and 84% (95% CI=69%-92%) and 89% (95% CI=83%-93%) for DWMRI, respectively. Low heterogeneity was found for sensitivity of TVUS but high for the specificity. For DW-MRI, the heterogeneity for specificity was low but the heterogeneity was significant for the sensitivity. In conclusion, the sensitivity and specificity of DW-MRI is higher compared to TVUS in assessing the deep myometrial invasion among women with endometrial cancer.